1987
DOI: 10.1136/bjo.71.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Management of unsuccessful lacrimal surgery.

Abstract: Two hundred and eight cases of failed dacryocystorhinostomy presenting to the Lacrimal Clinic at Moorfields Eye Hospital between 1970 and 1985 were reviewed. All cases underwent a further operation. The reasons for failure were usually apparent on reoperation. The surgical technique is described. A second dacryocystorhinostomy is a highly successful technique that spares both patient and surgeon the lifelong commitment to a bypass tube. At the time of operation the appropriate procedure was performed by a tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
166
1
5

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(182 citation statements)
references
References 9 publications
10
166
1
5
Order By: Relevance
“…Confirming the reported data, Welham et al 16 , reviewed 205 failed DCR and concluded that the main cause of failure was incomplete opening of rhinostome and Millman et al 17 observed that fibrotic sacs presented therapeutic failure in 29%, whereas sacs with mucoceles had 82% failure.…”
Section: Discussionmentioning
confidence: 64%
“…Confirming the reported data, Welham et al 16 , reviewed 205 failed DCR and concluded that the main cause of failure was incomplete opening of rhinostome and Millman et al 17 observed that fibrotic sacs presented therapeutic failure in 29%, whereas sacs with mucoceles had 82% failure.…”
Section: Discussionmentioning
confidence: 64%
“…If the bony ostium is small in a failed DCR, we have increased the size of the same ostium instead of making a new one keeping in mind that the ostium contracts after the operation [21]. The classical teaching on external DCR advises that the bony opening created at surgery be at least 15 mm in A-P diameter [22]. This teaching suggests that all bone between the medial wall of the sac and the nose should be removed leaving approximately an area of 5 mm around the internal punctum free of bone.…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting the current literature on CCO is problematic since previous studies commonly group all distal CCOs together, without clearly distinguishing between membranous and solid types. Furthermore, in the setting of primary DCR, distal canalicular obstruction remains among the most common etiology cited for failure, 1,7,[19][20][21] which in some cases, is because of the fact that the pre-operative evaluation fails to detect a canalicular obstruction before DCR surgery. 2,22 Although careful lacrimal probing and irrigation should reveal the 'soft-stop' in the setting of distal canalicular obstructions, the differentiation from a 'hard-stop' may on occasion be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Some techniques can be performed in an office setting, while others are used as an adjunct to more invasive lacrimal surgery. [2][3][4][5][6][7][8] In the setting of transnasal endoscopic dacryocystorhinostomy (EnDCR), one previous study has reported retrospective outcomes of trephination for CCOs. 9 To our knowledge, this is the first study that has employed membranectomy without trephination and has attempted to evaluate the outcome of both membranous and more solid distal obstructions of the common canaliculus.…”
Section: Introductionmentioning
confidence: 99%